Comics, memory and massive process of human rights violations. A brief review of Ibero-America - Caicedo Tapia, Danilo (2019)
This article explores the concepts of art and memory. Through them its importance, mutual relationship and social content are highlighted. Starting from the above, it makes a qualitative exploration, through the comic or comic strip, of the memory of several massive processes of human rights violations, occurred during the repression lived in Central America and South America between the decades of the fifties and nineties of the twentieth century, and in Spain with the Civil War and Franco’s dictatorship.The purpose of this study is to highlight the ethical and aesthetic role played by the comic art with respect to human rights, especially regarding the rights of victims to truth, justice and reparation. I conclude by pointing out as main findings that the comic is a cultural manifestation, artistic expression and mass media that contributes effectively to the preservation and construction of memory and even its potential as a narrative to resist and refute history and official truths.